RobustID: A Quantitative Framework for Evaluating the Resilience of Deep Learning Models Against Identity Manipulation - Suman Kumar Sanjeev Prasanna (International Journal of Intelligent Systems and Applications in Engineering, 2022)
As deep learning models increasingly govern operational identity verification, their vulnerability to sophisticated adversarial manipulation presents a critical risk to digital integrity. This research introduces RobustID, a comprehensive evaluation framework designed to quantify and enhance the resilience of neural identity detectors. The framework systematically applies a multi-vector attack taxonomy, including adversarial perturbations (PGD/FGSM), presentation attacks (PA), and cross-modal latent injections across diverse biometric and behavioral datasets. A core technical contribution of RobustID is the integration of Bayesian uncertainty estimation to quantify detection degradation and identify the breaking points of state-of-the-art verification architectures. Furthermore, the study evaluates strategic mitigation regimens, including adversarial training, feature-space regularization, and multimodal redundancy. Empirical results reveal that while standard models are highly susceptible to texture-based and resolution-aware spoofing, the implementation of the RobustID-derived adaptive defenses can substantially improve model robustness without compromising baseline accuracy. By bridging the gap between theoretical adversarial AI and practical security, this research establishes a definitive methodology for deploying resilient, confidence-aware deep learning systems in high-stakes operational environments